Firearm ownership among American veterans: findings from the 2015 National Firearm Survey - Emily C. Cleveland; Deborah Azrael; Joseph A. Simonetti; Matthew Miller (BMC, 2017)
Abstract Background While the majority of veteran suicides involve firearms, no contemporary data describing firearm ownership among US veterans are available. This study uses survey data to describe the prevalence of firearm ownership among a nationally representative sample of veterans, as well as veterans' reasons for firearm ownership. Methods A cross-sectional, nationally representative web-based survey conducted in 2015. Results Nearly half of all veterans own one or more firearms (44.9%, 95% CI 41.3-48.6%), with male veterans more commonly owning firearms than do female veterans (47.2%, 95% CI 43.4-51.0% versus 24.4%, 95%CI 15.6-36.1%). Most veteran firearm owners own both handguns and long guns (56.5%, 95% CI 51.1-61.8%); a majority cite protection as a primary reason for firearm ownership (63.1%, 95% CI 58.2-67.8%). Conclusions The current study is the first to provide detailed, nationally representative information about firearm ownership among U.S. veterans. Better understanding firearm ownership among veterans can usefully inform ongoing suicide prevention efforts aiming to facilitate lethal means safety among vulnerable veterans during at-risk periods.